(untitled) (Eurasian Journal of Philology Science and Education, 2023)
The article analyzes the current socio-linguistic issues of the state language. Compliance with the traditional norms of the national literary language, identification of the main trends in its development, compilation of description of new norms,collection and systematization of the ways of speech delivery in a communicative practice, in this regard, in accordance with the modern linguistic anthropocentric direction, determination, revision and clarification of the concepts of Kazakh speech culture and main scientific principles are the relevant issues. Due to the transition of the Kazakh alphabet to Latin graphics, further improvement of orthological codification of the Kazakh language has turned into one of the most acute problems in the scientific and methodological aspect. The unification and normalization of the language norm / literary norm contributes to improving the level of language culture of language users, enriching the language, as well as ensuring the full functioning of the Kazakh language as the state language. The article analyzes the relationship of the concepts of norm – language norm – literary norm, usus and the conceptual distinctive features, the peculiarities characterizing the norms, such as traditional and internal dynamic ones. The examples presented in the dictionary of erroneous uses “Soztüzer”, compiled collectively by the scientists like Sh.Kurmanbayuly, Zh.Zhakypov, T.Yermekova, O.Zhubayeva, B.Suyerkul, N.Kozhabek, A.Almenbet are traditionally analyzed. Moreover the frequency of use of a linguistic fact in determining the difference between norm and usus was taken as the main criteria.